Central motor conduction in patients with anti-ganglioside antibody associated neuropathy syndromes and hyperreflexia. Issue 5 (1st November 2002) - Oshima, Y; Mitsui, T; Yoshino, H; Endo, I; Kunishige, M; Asano, A; Matsumoto, T
Abstract : Objectives: Several serum antibodies against gangliosides are diagnostically important, particularly in Guillain-Barré syndrome (GBS), Miller Fisher syndrome (MFS), and multifocal motor neuropathy (MMN). Although hyperreflexia is an atypical symptom in these disorders, it has been found in some patients with GBS, MFS, and MMN. The aim of the study was to determine whether hyperreflexia corresponds to corticospinal tract dysfunction in these patients. Methods: The study examined central and peripheral motor conduction in patients with hyperreflexia who exhibited acute paralysis (group 1, n=5), acute ataxia and ophthalmoplegia (group 2, n=7), or chronic paralysis with conduction block (group 3, n=2). The clinical symptoms are similar to those in patients with GBS, MFS, and MMN, respectively, and serum anti-ganglioside antibodies were found to be positive in all patients. Using magnetic and electrical stimulation techniques, central and peripheral motor conduction were compared in patients in groups 1, 2, and 3 and patients with GBS (n=7), MFS (n=8), and MMN (n=6). Results: Central motor conduction times (CMCTs) in patients in groups 1, 2, and 3 were significantly delayed compared with those in patients with GBS, MFS, and MMN (p<0.01, p<0.05, p<0.05, respectively), and the delayed CMCTs significantly improved in the recovery periods (p<0.01, p<0.01, p<0.05, respectively). However, motor conduction velocity, compound muscle action potential, and F wave conduction velocity were not significantly different between the patients. Conclusion: These findings indicate that corticospinal tract is functionally involved in patients with anti-ganglioside antibody associated neuropathy syndromes and hyperreflexia